Predictive Role of Aortic Valve Calcium score on post-procedural outcomes and mortality after Transcatheter aortic valve replacement. (3rd October 2022) - Taskesen, T; Ahsan, M; Putz, J; Park, A; De Santis, T; Latif, A; Ugwu, J; Ellerman, M; Shivapour, D; Chawla, A; McAllister, D; Sigurdsson, G; et al.
Abstract: Introduction: Extent of aortic valve (AV) calcium increases as degenerative aortic valve stenosis progresses. Initial studies postulated AV calcium (AVC) score to be a predictor of complications such as need for pacemaker implantation, paravalvular regurgitation and mortality after Trans-catheter Aortic valve Replacement (TAVR). However, evidence regarding the impact of AVC score as a predictor of post-procedural complications and mortality has been conflicting. Objective: This study aimed to determine the prognostic impact of AVC as predictor of post-procedural outcomes and mortality in patients with severe aortic stenosis (AS) who underwent TAVR. Methods: We retrospectively abstracted the records of 497 patients with severe AS who underwent TAVR between January 2016 and July 2019 at our institution. All patients underwent a non-contrast cardiac CT scan on a Siemens Somatom Definition Flash 128 slice scanner. AVC score using the Agatston method was obtained retrospectively. Patients were divided into two groups: 1) Non-severe AVC score group [women <1200 Agatston unit (AU) and men <2000 AU]; 2) Severe AV Calcium Score group [women >1200 AU and men >2000 AU]. Primary outcome was 1-year mortality. Results: Among 466 patients included in the analysis, 352 patients were included severe AVC group while 114 patients were in the non-severe AVC group. Patients in the severe AVC group were older (81±8 vs 79±8 years), were predominantly males (79% vs 71%), and had less diabetes mellitus (31% vs 42%, p=0.02). Post-TAVR AV dimensionless index (0.58±0.13 vs 0.58±0.12, p=0.8) and AV mean gradient (9.5±4.9 vs 9.2±5.4 mmHg) were not statistically different between both groups. There was no statistical difference in the need for PPM (12% vs 7%, p=0.16), post-TAVR stroke (1.5% vs 0%), post-TAVR major complications (17.4% vs 10%, p=0.07), 30 day (3.7% vs 4.4%), and 1-year mortality (13.6 vs 11.4, p=0.6) between both groups. Conclusion: Our study report that the severity of AVC score does not have a prognostic impact on major post-procedural outcomes and mortality after TAVR. Funding Acknowledgement: Type of funding sources: None.